Estudo dos efeitos da inserção de óxido de grafeno nas propriedades térmicas, mecânicas e reológicas de nanocompósitos de poli(etileno tereftalato) - Diniz, Brenno Lavigne (2025)
In recent decades, polymer nanocomposites have attracted great scientific and industrial interest due to their remarkable characteristics in terms of combination of properties and/or improvement in processability with the addition of minimal amounts of nanofillers. Among thermoplastics, poly(ethylene terephthalate) – PET – stands out for its widespread usage in packaging, as well as industrial applications as an engineering plastic due to its excellent physical properties, such as mechanical strength, stiffness and gas barrier ability, which can be optimized through the incorporation of nanomaterials, such as graphene oxide (GO), as functional additives. In this context, the present study sought to measure the changes in thermal behavior, as well as in the mechanical and rheological properties of PET nanocomposites after incorporation of GO. For this purpose, PET nanocomposites with GO in different mass contents were produced by melt mixing in a co-rotating twin-screw extruder, incorporating into the polymer matrix GO synthesized by the Hummers method modified with ultrasonic exfoliation, and subsequently transferred to an appropriate organic solution based on rapeseed oil. GO was characterized by infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM). These characterizations revealed the presence of oxygenated functional groups, as well as an exfoliated structure with a corrugated morphology typical of this nanomaterial. The morphology of the nanocomposite suggests good dispersion of GO in the polymer matrix, as well as provide evidence of increased surface roughness with increasing GO content. Thermal analyses by differential scanning calorimetry (DSC) showed that GO acts as a nucleating agent, promoting the anticipation of PET crystallization upon cooling and reducing the cold crystallization temperature, without significantly altering the melting temperature at the studied nanofiller loads. A reduction in the glass transition temperature was also observed with increasing GO content, associated with a possible interference in the rigid amorphous fraction of the matrix, in addition to a reduction in the degree of crystallinity, a phenomenon of great industrial interest for the production process of plastic bottles. Nanoindentation measurements showed an increase in the elastic modulus, hardness and elastic behavior of the nanocomposites with increasing GO content, indicating effective structural reinforcement at low nanofiller concentrations. Rheological tests in the molten state indicated a reduction in complex viscosity with increasing GO content, suggesting better melt processability and a lubricating effect of the nanomaterial when incorporated into the polymer chains. These results highlight the multifunctional role of GO in PET matrices, acting simultaneously as a mechanical xvi reinforcement, thermal modifier and processing aid, and enabling the production of nanocomposites with optimized performance through a scalable and low-cost route based on the use of vegetable oil as a vehicle for transferring the nanomaterial to the polymer matrix in melt mixing processing.